(untitled) (Boca Raton, FL, 1993)
Beginning with an introduction to the systematics of fishes, this book goes on to discuss topics including: swimming and buoyancy mechanisms; the inner ear and lateral lines; electrosensation; anatomy and the physiology of the cardiovascular system; and osmoregulation.
Keywords: Fishes; Physiology